Study on in vitro propagation of \(Vaccinium myrtillus\) Linn. via nodal culture method - Thanh Hang, Nguyen Thi; Phuong Hoang, Nguyen Thi; Van Khiem, Dinh; Xuan Huyen, Phan (Academia Journal of Biology, 2022)
Vaccinium myrtillus Linn. is an imported fruit tree with high economic value. Currently, in Vietnam there has not been any publication on in vitro propagation of the blueberry plant. This study is focused on in vitro propagation of V. myrtillus by nodal culture. The results showed that in vitro shoot growth and proliferation were the best when nodes were cultured on WPM medium supplemented with 0.5 mg/L zeatin, 30 g/L sucrose, 10 g/L agar, pH 5.8 (shoot height 4.24 cm, 1 shoot/explant, 8.60 nodes/shoot). The third nodes to sixth nodes proved to be suitable materials for in vitro propagation of V. myrtillus. The proliferation and growth of shoots on the medium without activated charcoal (plant height 3.92 cm, 1 shoot/explant, 8.60 nodes/shoot) were better than those grown on the medium supplemented with 1 g/L of activated charcoal (plant height 3.64 cm, 1 shoot/explant, 7.90 nodes/shoot). For the in vitro rooting stage, the WPM medium containing 1.0 mg/L IBA, 30 g/L sucrose, 10 g/L agar, pH 5.8 resulted in plant height 5.49 cm, root length 1.42 cm, root formation rate 100%. After transferring the cultivated-tissue Vaccinium myrtillus to the greenhouse, substrate with coconut fibre powder, the results were observed to be plant height 6.94 cm, root length 3.18 cm, survival rate 95%. The plantlet growth increased overtime after 4 months in the greenhouse.